Evolutionary and ecological forces that shape the bacterial communities of the human gut - Messer, Jeannette S. (Mucosal Immunol, 2017)
Since microbes were first described in the mid-1600's, we have come to appreciate that they live all around and within us with both beneficial and detrimental effects on nearly every aspect of our lives. The human gastrointestinal tract is inhabited by a dynamic community of trillions of bacteria that constantly interact with each other and their human host. The acquisition of these bacteria is not stochastic, but determined by circumstance (environment), host rules (genetics, immune state, mucus, etc), and dynamic self-selection among microbes to form stable, resilient communities that are in balance with the host. In this review, we will discuss how these factors lead to formation of the gut bacterial community and influence its interactions with the host. We will also address how gut bacteria contribute to disease and how they could potentially be targeted to prevent and treat a variety of human ailments.